Memahami aliran teologi islam : mu’tazilah, sejarah dan ajarannya - NAVISAH, DEWI (Maliki Interdisciplinary Journal, 2024)
The Mu'tazilah school is one of the oldest and largest theological schools in Islamic history that played an important role in the development of Islamic philosophy, religion, and Islamic historical thought. The school emerged in the early 2nd century Hijri in the city of Basrah, the centre of Islamic science and civilisation at the time, which became a meeting place for various cultures and religions. The Mu'tazilah became famous for their controversial fatwas that took the Islamic world by storm for about 300 years. During this period, conflicts with Ahlussunnah wal Jamaah scholars of different views often led to violence and bloodshed. This article aims to explore the history, teachings and influence of the Mu'tazilah school in the context of Islamic thought.